The Effect of Executive Characteristics and Financial Constraints on Tax Avoidance: - Shifa Nabila; Nurul Aisyah Rachmawati (Journal of Accounting, Business and Management (JABM), 2023)
This study aimed to examine the effect of executive characteristics and financial constraints on tax avoidance. our proxies for Executive characteristics are a corporate risk, and the proxy for the financial constraint is FINCON value using confirmatory analysis of combines these three measures net debt ratio, interest coverage ratio, and dividend payout ratio. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange on the observation period 2016- 2018. The method used is purposive sampling, with a total of samples obtained were 135 manufacturing companies during 2016-2018. The type of data used is secondary data taken from www.idx.co.id. Data analysis was processed using multiple linear regression. The results showed that executive characteristics had a positive and significant effect on the company’s tax avoidance. Financial constraints have a positive and significant effect on the company’s tax avoidance on manufacturing companies listed on the Indonesia Stock Exchange period 2016-2018.